Seasonal variation of PM2.5 and PM10 in urban and remote regions of Nepal - Chalise, Ramesh; Sharma, Surendra; Chalise, Baburam; Prakash Chalise, Laba; Narayan Yadav, Shiv (Himalayan Physics, 2025)
Air pollution is a serious environmental problem that affects the health of people, animals, and the natural environment. It is mainly caused by human activities such as vehicle emissions, industrial work, waste burning, and construction dust. Breathing polluted air can lead to asthma, lung problems, heart disease, and other serious health issues. In cities like Kathmandu, air pollution is increasing due to rapid urban growth and traffic, while remote areas often have cleaner air. This study compares air quality between an urban site (Ratnapark, Kathmandu) and a remote site (Rara Lake, Mugu) in Nepal using PM2.5 and PM10 measurements for 2023. Ratnapark exhibited much higher pollution, with peak PM2.5 of 97.97 μg/m3 and PM10 of 137.33 μg/m3 in February, while Rara Lake remained relatively clean, with most PM2.5 and PM10 values below 20 μg/m3. The lowest pollution at both sites occurred during the rainy season. The PM2.5/PM10 ratio analysis revealed that finer particles were more dominant at the urban site, whereas coarser particles prevailed in the remote area. These results highlight the significant contrast in air quality between urban and remote regions and the influence of seasonal weather and human activities on pollution levels.